1972
DOI: 10.1159/000459500
|View full text |Cite
|
Sign up to set email alerts
|

Liver Enzymes in the Eck Fistula Rat

Abstract: The paper considers whether shunting of portal blood around the liver and decreased total hepatic blood flow are sufficient to explain the degree of hyperammonemia occurring after portacaval shunt (PCS). For this purpose, urea-cycle enzymes, transaminases, and glutamatedehydrogenase were measured in rat-liver homogenates 10, 20, and 30 days after PCS and compared to unoperated controls. In view of the marked postoperative reduction of liver mass, three typical responses could be observed : type I, normal or sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…This implies a PCS which functions well. The changes have also been observed in this series ( Table 2) and were of the same order of magnitude as described in former studies (7,15). GGTP activity after PCS rose significantly compared with that of adult control animals (Table 3).…”
Section: Ggtp After Pcssupporting
confidence: 89%
See 2 more Smart Citations
“…This implies a PCS which functions well. The changes have also been observed in this series ( Table 2) and were of the same order of magnitude as described in former studies (7,15). GGTP activity after PCS rose significantly compared with that of adult control animals (Table 3).…”
Section: Ggtp After Pcssupporting
confidence: 89%
“…In shunted animals, a decrease in liver and body weight during the first days after the operation has been a general experience in this and other laboratories (1,7,15,19). This implies a PCS which functions well.…”
Section: Ggtp After Pcsmentioning
confidence: 76%
See 1 more Smart Citation
“…The general findings such as hyperam monemia, changes in body and liver weight (table 1) occurring after PCS have been de scribed previously (5)(6)(7)9). Under the dietary treatment used in these experiments, the body weights were not lower than those of the control group 10 days after PCS, whereas the liver weights were significantly diminished (p < 0.05).…”
Section: Resultssupporting
confidence: 61%
“…It was prima rily chosen to study different enzymatic reac tions involved in ammonia detoxication. Previous studies on enzymes of the urea cycle, of the pyrimidine pathway as well as on enzyme reactions involved in glutamic acid metabolism, showed that they are affected by elevated systemic ammonia concentrations (5)(6)(7).…”
mentioning
confidence: 99%